Influence of Vitamin D Deficiency on the Level of Salivary cathelicidin LL-37 in relation to Dental Caries Experience: A Case-Control Study - Alhelfi, Narjes M.; Hobi , Nibal M. (AL-Kindy College Medical Journal, 2023)
Background: Vitamin D improves innate immunity by enhancing the expression of antimicrobial peptides. The antimicrobial action of cathelicidin is widespread and effective against cariogenic bacteria. This research aimed to investigate the effect of vitamin D deficiency on the level of salivary cathelicidin concerning dental caries experience. Subjects and Methods: A case-control study was carried out, and the sample was composed of 80 females; the study group involved 40 females with a serum vitamin D concentration of less than 10 ng/ml. In addition to the control group involving 40 females who matched the case in number and age but serum vitamin D concentration of 30 ng/mol or more, their age range was 20-30 years. WHO 2013 index was used for the assessment of dental caries experience, and collection of unstimulated saliva was done to measure salivary cathelicidin. Results: Data from the current study showed that the mean values of the Decayed, Missing, and Filled Teeth index and its components (Decayed Teeth, Missing Teeth) were higher in the study group than those in the control one, with a significant difference for Decayed Teeth. Salivary cathelicidin was higher in the control group with a statistically significant difference. Conclusion: It was confirmed that serum vitamin D status and salivary cathelicidin levels are related. Vitamin D deficient patients who had higher Decayed, Missing, and Filled Teeth index values expressed a lower level of salivary cathelicidin than the control group.